Effect of silicon carbide and silicon carbide/alumina reinforced aluminum alloy (AA6061) metal matrix composite. (2021) - Chandradass, J.; Thirugnanasambandham, T.; Jawahar, P.; Kannan, T.T.M.
Abstract: AA6061 matrix composites are becoming indispensable in automotive, aircraft, marine, and structural applications because of their lightweight, good mechanical, corrosion, and wear resistance properties compared to traditional materials. The present study evaluates the effect of silicon carbide and silicon carbide/alumina particle with 5 wt% SiCp, 7 wt%SiCp, and 7 wt%SiCp /3 wt% Al2 O3 on the mechanical, microstructural, and wears performance of prepared composites. The additions of reinforcement increases the mechanical and wear resistance of composites compared to cast aluminum alloy. The AA6061 alloy with 7 wt%SiCp /3 wt% Al2 O3 composite has obtained a maximum tensile strength, hardness and wear resistance of 134.3 N/mm 2, 35VHN and 17.27 × 10 -5 mm 3 /Nm, respectively. The optical micrograph shows the dispersion of reinforcement particles is uniform throughout the aluminum alloy matrix.